Risk factors for multivessel coronary lesion in patients with coronary artery disease and primary hypothyroidism - A.R. Muneer; A.N. Sumin; A.S. Ankudinov (Известия высших учебных заведений. Поволжский регион: Медицинские науки)
Background. The association of hypothyroidism with ischemic heart disease (CHD) is an aggravating factor of the course for the main cardiovascular pathology. The data available in the modern literature on the effect of hypothyroidism on the factors of the course of coronary heart disease are contradictory. The purpose of this study is a comparative analysis of laboratory and instrumental data taken into account during coronary artery disease in patients with and without hypothyroidism and the search for possible associations of thyroid hormone levels with indicators of the state of the coronary bed. Materials and methods. 240 patients with coronary heart disease were examined. The study group consisted of 90 patients with coronary heart disease and hypothyroidism, the comparison group – patients with coronary heart disease without thyroid pathology ‒ 150. A comprehensive examination of patients, including coronary angiography, was carried out. The frequency of cases and characteristics of lesions of the coronary bed, possible associations of thyroid hormones with factors of progression of atherosclerosis of the coronary arteries were evaluated. Results. The study revealed significant changes in the lipid spectrum, the severity of myocardial ischemia according to ECG, as well as the frequency of occurrence of multivessel lesions of the coronary bed in the group of patients with hypothyroidism and coronary artery disease compared with patients with coronary artery disease without hypothyroidism. The identified factors had a statistically significant association with thyroid hormones in the group of patients with coronary heart disease and hypothyroidism. Conclusions. The presence of hypothyroidism in patients with coronary artery disease, especially long-term existing, should be considered as an additional factor in the deterioration of the coronary bed and the course of coronary artery disease.